Research on the Rheological Properties of Asphalt Binder Modified by Fume Silica and Crumb Rubber Compound - Akpolat, Mustafa; Kok, Baha Vural; Aydogmus, Ercan (Budapest Univ Technology Economics, 2022)
This study investigates the effect of using Fume Silica (Aerosol 300) alone and together with crumb rubber (CR) in bitumen modification on the traditional and rheological properties of the binder and compares it to the SBS modified binder. Using the aerosol additive in the binder at the rates of 0.5%, 1%, 1.5%, and 2% were determined as the most convenient ratio and CR+aerosol modified binders were prepared per this ratio. The binders were subjected to the softening point, viscosity, frequency sweep, bending beam rheometer (BBR), and Fourier Transform Infrared spectroscopy (FTIR) tests in the context of the study. Besides, the optimum conditions were determined according to the response functions by designing an experiment with statistical regression according to the Response surface methodology (RSM). The results indicate that the optimum aerosol ratio is 1.5%. With the use of 1.5% aerosol in 6% CR modification per bitumen weight, it was found that (1) the softening point increases and the temperature sensitivity decrease in comparison to other binders, (2) the consistency of the binder increases, (3) the complex modulus values increase and become more resistant to rutting, (4) the low-temperature parameters enhance by performing more flexible behavior, (5) there may be physical changes in the structure even though there is no chemical reaction in the binder with the use of CR and aerosol additives, and (6) the experimental data and theoretical data obtained from the RSM method are consistent as per the statistical analysis.
Keywords: fume silica; crumb rubber; modification; rheology; response surface methodology